RESISTANCE PROFILE OF BACTERIA ISOLATED FROM LAYING HENS MANURE IN JEMBER REGENCY - Suswati, Enny; Sakinah, Elly Nurus; Firdaus, Jauhar; Khoiri, Abu (Buletin Veteriner Udayana, 2023)
Antibiotics are becoming more prevalent as environmental pollutants, raising public health concerns. Antibiotics are routinely employed as growth promoters and therapeutic agents in poultry feeds. Because antibiotics are not completely metabolized in chicken body tissues, they are deposited in meat as parent compounds and eventually extruded into the environment via fowl droppings. Organic fertilizers based on chicken litter are typically recycled into the soil to improve the structure and fertility of agricultural land. Chicken litter, a vital source of nutrients for crop productivity, may also carry a variety of human infections that might endanger humans who consume contaminated food or water. A convenience sampling of five places was carried out. Litter samples were collected aseptically. CLSI standards were used to isolate E. coli and Proteus spp. The disc diffusion method was used to determine antibiotic susceptibility. E. coli and Proteus spp. were found in 80% and 60% of the samples. All E. coli and Proteus spp isolates derived from laying hen manure were resistant to sulfamethoxazole, ciprofloxacin, cefixime, tetracycline, amoxiclav, ceftriaxone, and chloramphenicol. However, only 50% and 33% were resistant to azithromycin. All E. coli and Proteus spp. Isolates were multidrug resistant. There was no resistance reported to cefepime or imipenem. Contamination of chicken litter with multidrug-resistant E. coli and Proteus spp. may be an underappreciated source of antimicrobial resistance (AMR) transmission to animals, people, and the environment. This demonstrates the importance of a One Health strategy to AMR surveillance and control in Jember. Monitoring AMR hazards and trends in the chicken litter would be possible with ongoing surveillance.